Mitigasi Bias Feedback Loops dalam Rekomendasi Buku Menggunakan Pendekatan Causal Adjustment - Yohanes Andika Dharma; Daniel Udjulawa (TIN: Terapan Informatika Nusantara, 2026)
The digital publishing industry has experienced exponential growth over the past decade, with platforms such as Goodreads and Amazon cataloging over 50 million book titles available online (Ricci et al., 2022). This abundance of choices paradoxically creates difficulty for users to discover books that genuinely match their preferences. The book domain was specifically chosen due to its unique characteristics: a highly asymmetric consumption distribution (bestsellers dominate 80% of sales despite representing only 5% of titles), extreme genre and language diversity, and readers' need for intellectual exploration beyond mere popularity. Collaborative filtering-based recommender systems address this challenge but are vulnerable to feedback loops that reinforce popularity bias, causing popular books to receive excessive exposure while long-tail items are neglected. This problem is exacerbated by Missing Not at Random (MNAR) data. This study proposes CAFL-SVD, a Matrix Factorization model based on SVD integrated with the CAFL algorithm through IPS and K-Means cluster regularization. Evaluated on Book-Crossing dataset with 585,579 ratings, CAFL-SVD reduces Gini coefficient by 37.7% (0.5783 to 0.3601), achieves peak NDCG@5 of 0.6207, maintains 100% coverage, and average Novelty Score of 14.0, demonstrating that causal approaches can simultaneously improve recommendation fairness and relevance without significant accuracy sacrifice.